Online collaborative writing: students’ perception / Mohammed Abdel Hakim Farrah - Hakim Farrah, Mohammed Abdel (Universiti Teknologi MARA, Kedah, 2015)
This study investigated the attitudes of an English writing class towards online collaborative learning activities. A 20-item questionnaire was used to assess the students’ attitudes towards this experience. The participants of the study consisted of 55 students studying a Writing II course. There were two sections; one control and the other is experimental. The researcher investigated whether there were significant differences in the attitudes of the students pertaining to, group (experimental vs. control), gender, grade (GPA), access to the Internet and anxiety. The results indicated that the experimental group held positive attitudes towards the online collaborative learning experience. Moreover, the results showed that there were statistically significant differences between anxious learners and the learners who do not have anxiety towards online collaborative activities. In addition, students who had regular access to the Internet had better attitudes for the online collaborative activities. However, no statistically significant differences were revealed regarding the grade of the students. This means that low achievers and advanced learners held similar attitudes towards the online experience. Finally, no statistically significant differences were shown based on gender.